История Древнего Востока (1979)
Kuziščin, V. I. (Hrsg.), Geschichte des Alten Orients; Hochschul-Lehrbuch; S. 92-270 Vorderasien, S. 272-314 Iran; Mitarbeit von M. A. Dandamajev, V.M. Masson, D.G. Reder, u. A.